ANALISA HERMENEUTIK PADA TEKS TATA UPACARA TULUDE WARGA DIASPORA SANGIHE DI DESA SEREI - Djakaria, Salmin (HOLISTIK, Journal Of Social and Culture, 2018)
For Sangirese, Tulude is the one of the most important ceremony and ritual, this is not only happened for those who lived in the Sangihe island but also to those who lived in diasporic area, especially in the mainland of North Sulawesi. This article aims to describe the content of Tulude ritual and its meaning for sangirese and analyze the meaning of its content using hermeneutical based theory. The locus of this article were taken in Serei, a village in North Minahasa regency, a place with predominantly Sangirese society but also with an aculturation in term of their religious way of life with people of Minahasa and influenced by Gereja Masehi Injili di Minahasa (GMIM).Â Keywords: Tulude, Hermeneutic, Sangirese, Serei